Audit of lower urinary tract endoscopic procedures in Borno, North-Eastern Nigeria - Tela, Usman M.; Lawn, Abdu M.; Mohammed, Ahmed A.; Dogo, Hassan M.; Ghide, Bukhari A. (International Journal of Research in Medical Sciences, 2021)
Background: Endourology which includes lower urinary tract (LUT) endoscopy, is an important component of standard urological practice worldwide. The objective of our study was to audit the LUT endoscopic procedures performed in Borno, a state in north-eastern Nigeria and share our experience. Methods: We, retrospectively reviewed the Lower urinary Tract endoscopies performed in Borno state over 9 years, from January 2012 to December 2020. Data related to LUT endoscopies were extracted from the patients’ clinical notes and operation theatre registers of the 2 focused hospitals in Borno where endourology procedures were performed (University of Maiduguri Teaching Hospital and Royal specialist hospital maiduguri) and then analyzed. Urology patients who did not undergone LUT endoscopy were excluded. Results: We analyzed the data of total sum of 201 patients for the 2 hospitals, which represented the sample size for the study. Mean age of patients was 47.2years, with male to female ratio of 3.5:1. Bladder tumor with or without haematuria (31.3%) was the commonest indication for LUT endoscopy, seconded by removal of ureteric double J stents (23.4%). Urethrocystoscopy (74.0%) was the commonest procedure performed predominantly under local anaesthesia, for both diagnostic and therapeutic purposes. Conclusions: We reported LUT endoscopies in Borno which was commonly indicated in bladder tumors presenting with or without haematuria. Urethrocystoscopy is the commonest procedure. As we get more endourology equipment in the public hospital many of our patients will benefit from these minimally invasive procedures in both lower and upper urinary tract diseases.